The glorification of the Creator in Yusuf Balasagun’s «Kutadgu bilig» - Nuriman, Бекарыс; Eker, Суер (Turkic Studies Journal, 2022)
The accepting of Islam by the Turkic peoples in the era of the Karakhanids was widely reflected in literary monuments. One of these monuments, which highlights some issues of Islam, is Yusuf Balasugin’s Kutadgu Bilik. Since then, the religious theme in literature, its connection with literary processes in the literary criticism of the Turkic peoples has been relevant and in demand, which is confirmed by the studies of such scientists as R.R. Arat, S.M. Arsal, I. Kafesoglu, A. Inan, A. Dilashar, A.B. Yerzhilasun, R. Dankoff, N. Kelimbetov, A. Kyraubaeva, A. Egeubaev, S. Eker, H. Kasapoglu, G. Kurmangalieva, G. Kanasheva. This article examines the image of the Creator-God in Yusuf Balasaguni’s “Kutadgu Bilik”. As an object of study, the authors use a facsimile of the Fergana version of the monument in a transcription performed by R.R. Arat. In the process of research 33 baytes were studied, fourteen of which are given as illustrations. The meanings of religious words are revealed on the basis of various points of view and compared with the texts of the Koran. To determine the frequency of use of religious terms in the article, the method of quantitative analysis was used.